Changes and Disturbance in Tropical Rainforest in South-East Asia 2000
DOI: 10.1142/9781848160125_0005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selective logging on the distribution of moths in a Bornean rainforest

Abstract: The e¡ects of selective logging on the diversity and species composition of moths were investigated by sampling from multiple sites in primary forest, both understorey and canopy, and logged forest at Danum Valley, Sabah, Malaysia. The diversity of individual sites was similar, although rare¢ed species richness of logged forest was 17% lower than for primary forest (understorey and canopy combined). There was signi¢cant heterogeneity in faunal composition and measures of similarity (NESS index) among primary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Previous studies have reported a high proportion of moth singletons in forest habitats (WILLOT 1999, RICKETTS et al 2001, BREHM et al 2003, HILT & FIEDLER 2005. We suggest that the relatively low density of individuals in the grassland is the most probable factor accounting for the observation of a higher proportion of singletons in this habitat.…”
Section: Differences Among Vegetation Formationssupporting
confidence: 47%
“…Previous studies have reported a high proportion of moth singletons in forest habitats (WILLOT 1999, RICKETTS et al 2001, BREHM et al 2003, HILT & FIEDLER 2005. We suggest that the relatively low density of individuals in the grassland is the most probable factor accounting for the observation of a higher proportion of singletons in this habitat.…”
Section: Differences Among Vegetation Formationssupporting
confidence: 47%
“…For example, in the Amazon litter beetles need more than 1 km 2 of intact forest to subsist (Didham 1997). The above considerations may apply only to insect herbivores in the understorey (for canopy insects see Willott 1999). In sum, we found some support for RIL from a conservation viewpoint and, above all, for promoting studies that examine how best RIL could minimize the loss of biodiversity in tropical wet forests.…”
Section: mentioning
confidence: 62%
“…(Holloway, Kirk-Spriggs & Chey 1992;Hill et al . 1995;Hill 1999;Intachat, Holloway & Speight 1999;Willott 1999;Vasconcelos, Vilhena & Caliri 2000;Davis et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Forest degradation is broadly defined as the long-term reduction of the overall potential supply of goods and services, including carbon storage, wood production, and biodiversity conservation. The impacts of individual forms of tropical forest degradation are understood in outline; for example, industrial logging reduces carbon stocks (3)(4)(5) and changes biodiversity, often reducing it (5)(6)(7)(8). Deforestation and degradation patterns have been related to road access, road density, topography, and biophysical characteristics such as soil fertility (9)(10)(11)(12)).…”
mentioning
confidence: 99%